147k views
4 votes
Plato!! Please help!!!

Plato!! Please help!!!-example-1

1 Answer

3 votes

Answer:


a =7
b = 2
c = -4

Explanation:

Given


(3x)/(x + 2) + (4x)/(x - 2) = (ax^2 + bx)/(x^2 + c)

Required

Find a, b and c


(3x)/(x + 2) + (4x)/(x - 2) = (ax^2 + bx)/(x^2 + c)

Take LCM


(3x(x -2) + 4x(x+2))/((x + 2)(x - 2)) = (ax^2 + bx)/(x^2 + c)

Expand


(3x^2 -6x + 4x^2+8x)/(x^2 - 4) = (ax^2 + bx)/(x^2 + c)

Collect like terms


(3x^2 + 4x^2-6x+8x)/(x^2 - 4) = (ax^2 + bx)/(x^2 + c)


(7x^2+2x)/(x^2 - 4) = (ax^2 + bx)/(x^2 + c)

By direct comparison:


ax^2= 7x^2 \to a = 7


bx = 2x \to b = 2


-4 = c \to c = -4

User Meim
by
5.3k points